Alternative Education Global Perspectives Relevant to the Asia-Pacific Region - Nagata, Yoshiyuki; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Alternative streams of education have been and remain an important but difficult theme for teachers, parents, policy-makers, and scholars. By focusing on case studies of six countries (Bolivia, Thailand, Australia, USA, The Netherlands, and Denmark), and by comprehensively analysing these by means of international comparative methodologies, the author approaches the nuts and bolts issues of alternative and mainstream education systems. The case studies include Charter Schools in the USA and Waldorf Schools in Australia. The study presents not only an insightful analysis of alternative forms of education with regard to actual issues in societies and also legal and administrative features of education. It provides insights into the kind of school development that could be appropriate in the 21st century and the types of educational communities we should seek to create in the age of globalisation.
Alternative Education: An Overview -- Case Study: Bolivia A Free School at the Foot of the Andes -- Case Study: Thailand Alternative Schools in a Society Developing the Legal Framework for a Pluralistic Educational System -- Case Study: Australia Issues in Support Mechanisms Involving Alternative Schools -- Case Study: The Netherlands Alternative Education Shaken by Changes in its Basic Foundation -- Case Study: The State of Oregon in the United States of America A Pluralistic Education System and Alternative Education Supported by the Law and the Key Initiators -- Case Study: Denmark Alternative Education Fostered by Support Mechanisms Cultivated Through the History of the Common People -- How Much Alternative Education Is There? -- Quality Assurance in Alternative Education: Current Circumstances and Issues -- The State of Alternative Education in Different Countries.
Keywords: EDUCATION; COMPARATIVE EDUCATION; EDUCATION AND STATE; EDUCATION; EDUCATION & SOCIETY; EDUCATIONAL POLICY; LEADERSHIP & ADMINISTRATION; COMPARATIVE EDUCATION